The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.2319/010417-12.1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic reliability of mandibular second molar maturation in the identification of the mandibular growth peak: A longitudinal study

Abstract: Objective: To investigate the diagnostic reliability of mandibular second molar maturation in assessing the mandibular growth peak using a longitudinal design. Materials and Methods: From the files of the Burlington and Oregon growth studies, 40 subjects (20 from each collection, 20 males and 20 females) with at least seven annual lateral cephalograms taken from 9 to 16 years were included. Mandibular second molar maturation was assessed according to Demirjian et al., and mandibular growth was defined as annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…Although eruption is under significant control of genetics, it may be affected by a myriad of systemic and local factors, including but not limited to, nutrition, tooth size-arch length discrepancy, dental caries, early tooth loss, and many other factors. Having said that, using tooth formation stages has shown limited reliability, 4,5 while promising correlations were shown when using diagnostic performance of eruption stages in the identification of skeletal maturity. 6,14,15 Based on these results, it could be concluded that the early permanent stage of eruption showed strong diagnostic accuracy for predicting of the cessation of the pubertal growth spurt.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Although eruption is under significant control of genetics, it may be affected by a myriad of systemic and local factors, including but not limited to, nutrition, tooth size-arch length discrepancy, dental caries, early tooth loss, and many other factors. Having said that, using tooth formation stages has shown limited reliability, 4,5 while promising correlations were shown when using diagnostic performance of eruption stages in the identification of skeletal maturity. 6,14,15 Based on these results, it could be concluded that the early permanent stage of eruption showed strong diagnostic accuracy for predicting of the cessation of the pubertal growth spurt.…”
Section: Open Accessmentioning
confidence: 99%
“…For this reason, many studies have investigated multiple potential indicators of skeletal maturity. [3][4][5] Some of these indicators, such as chronological age, 3 proved unreliable, while others, such as dental maturity (tooth-formation stages) 4,5 of permanent lower canines and second molars, has shown limited reliability. Researchers have argued that studying the relationship between stages of dentition, or dental eruption (teeth entering the oral cavity and becoming visible), and skeletal maturity is useful in clinical practice and for interpreting results of studies reporting treatment outcomes at different dentition stages.…”
mentioning
confidence: 99%
“…A Demirjian-féle módszer kormeghatározásra használható diagnosztikus megbízhatóságának igazolására elsősorban a kézcsont-, illetve a csigolyaérettségi vizsgálómódszereket alkalmazzák. A kapott eredmények azonban meglehetősen ellentmondásosak [24][25][26][27][28][29]. A nyakcsigolyák tekintetében Kumar és mtsai [24], Giri és mtsai [25] továbbá Cossellu és mtsai [26] is szoros összefüggést mutattak ki a Demirjian-féle fogazati korok és a csontérettségi korok között.…”
Section: áBraunclassified
“…A nyakcsigolyák tekintetében Kumar és mtsai [24], Giri és mtsai [25] továbbá Cossellu és mtsai [26] is szoros összefüggést mutattak ki a Demirjian-féle fogazati korok és a csontérettségi korok között. Nayak és munkacsoportja [20] ÖSSZEFOGLALÓ KÖZLEMÉNY találták, hogy a szkeletális kor és a várható növekedés nem áll kapcsolatban a fogak kalcifikációs szintjeivel [27][28][29]. A jelenleg rendelkezésre álló adatok alapján úgy tűnik, hogy más módszerek hatékonyabb eszközként szolgálnak a csontérettség és a növekedési csúcsok meghatározásában.…”
Section: áBraunclassified
“…In Dentistry, maxillofacial surgery, orthodontics and skeletal orthopedics figure as important fields in the treatment of functional and aesthetic growth disorders. The therapeutic approaches in these fields often require radiographic analysis is to screen skeletal morphology and to intercept skeletal disorders with optimal timing ( 6 ). The analysis of skeletal development through carpal radiographs was a common practice along the last decades ( 7 ).…”
Section: Introductionmentioning
confidence: 99%